Seksisme dan Misogini dalam Rubrik “Oi Mak Jang!” Harian Media 24 Jam - Eko Agus Herianto (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to determine the value of sexism and misogyny in the rubric “Oi Mak Jang!” Harian Media 24 Jam uses the theory of Critical Discourse Analysis (CDA) Sara Mills and Lorrine Code. This study uses a qualitative descriptive method that has a function substantive namely describing and describing data through words, sentences, or comprehensive analysis. This research looks at how women are positioned in a journalistic work, especially feature journalism. Through the study of Sara Mills' Critical Discourse Analysis (AWK) in analyzing discourse contained in the rubric "Oi Mak Jang!", it was found that the rubric it contains: 1. Subject-object positions that place a lot of positions women as characters told in vulgar languages, 2. The value of sexism is either overt or covert/indirect that it presents with clearly an unfair distinction between the sexes, 3. Misogyny values ??that showing hatred towards women in the form of slander, sexual discrimination, and sexual objectification.